Adsorption by carbons - Bottani, Eduardo J.; Tascón, J. M. D. (Elsevier, 2008)
This book covers the most significant aspects of adsorption by carbons, attempting to fill the existing gap between the fields of adsorption and carbonaceous materials. Both basic and applied aspects are presented. The first section of the book introduces physical adsorption and carbonaceous materials, and is followed by a section concerning the fundamentals of adsorption by carbons. This leads to development of a series of theoretical concepts that serve as an introduction to the following section in which adsorption is mainly envisaged as a tool to characterize the porous texture and surface chemistry of carbons. Particular attention is paid to some novel nanocarbons, and the electrochemistry of adsorption by carbons is also addressed. Finally, several important technological applications of gas and liquid adsorption by carbons in areas such as environmental protection and energy storage constitute the last section of the book. - the first book to address the interplay between carbonaceous materials and adsorption - includes important environmental applications, such as the removal of volatile organic compounds from polluted atmospheres - covers both gas-solid and liquid-solid adsorption.
Keywords: Carbon -- Absorption and adsorption.; elektronické knihy; electronic books